Assistive technology and schizophrenia. Issue 2 (27th June 2019) - Devlin, Hannah; Nolan, Clodagh; Turner, Niall
Abstract : Purpose: Assistive technology (AT) has been highlighted as a tool that can support self-management for people living with schizophrenia. A gap in the literature exists regarding the views held by the stakeholders involved in the health care of an individual living with schizophrenia regarding the potential use of AT to enable the self-management of this condition. The purpose of this paper is to explore how individuals living with schizophrenia, their relatives and their mental health care professionals view AT as a tool to facilitate self-management. Design/methodology/approach: This mixed methods research paper will discuss the findings of the second stage of a two-stage research study. The paper will discuss the findings of questionnaires that were disseminated to service users living with schizophrenia, their relatives and the health-care professionals of a community mental health service in the Greater Dublin area. Findings: The results indicate that the introduction of AT for the self-management of schizophrenia would be accepted by key stakeholders. Research limitations/implications: As AT continues to develop, it is clear from the findings presented in this paper that the main stakeholder groups involved in the care of an individual living with schizophrenia are amenable to the use of AT to facilitate the self-management of this condition. Further research is required to explore correct policing and management of its implementation. Originality/value: This study is the first study of its kind within an Irish context to explore the use of assistive technology as a tool for self-management from the perspective of those experiencing schizophrenia, their relatives and the health-care professionals working alongside them.